2021
DOI: 10.3389/fneur.2021.718438
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Carotid MRI for Personalized Ischemic Stroke Risk Prediction in Patients With Carotid Artery Stenosis

Abstract: Rupture of a vulnerable carotid plaque is an important cause of ischemic stroke. Prediction models can support medical decision-making by estimating individual probabilities of future events, while magnetic resonance imaging (MRI) can provide detailed information on plaque vulnerability. In this review, prediction models for medium to long-term (>90 days) prediction of recurrent ischemic stroke among patients on best medical treatment for carotid stenosis are evaluated, and the emerging role of MRI of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Furthermore, 3-D ultrasound may evaluate carotid plaque surface and may identify carotid ulcers, which are associated with a higher incidence of long-term stroke or death [216,217]. By using multiple different high spatial resolution contrast weightings, MRI/MRA has the advantage of being able to measure all the hallmarks of carotid plaque vulnerability, namely carotid plaque burden, intraplaque hemorrhage, ulcerations, lipid-rich necrotic core, and thin or ruptured fibrous cap [218]. These imaging parameters could be included in a clinical risk prediction model to determine a more personalized stroke risk [218].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 3-D ultrasound may evaluate carotid plaque surface and may identify carotid ulcers, which are associated with a higher incidence of long-term stroke or death [216,217]. By using multiple different high spatial resolution contrast weightings, MRI/MRA has the advantage of being able to measure all the hallmarks of carotid plaque vulnerability, namely carotid plaque burden, intraplaque hemorrhage, ulcerations, lipid-rich necrotic core, and thin or ruptured fibrous cap [218]. These imaging parameters could be included in a clinical risk prediction model to determine a more personalized stroke risk [218].…”
Section: Discussionmentioning
confidence: 99%
“…By using multiple different high spatial resolution contrast weightings, MRI/MRA has the advantage of being able to measure all the hallmarks of carotid plaque vulnerability, namely carotid plaque burden, intraplaque hemorrhage, ulcerations, lipid-rich necrotic core, and thin or ruptured fibrous cap [218]. These imaging parameters could be included in a clinical risk prediction model to determine a more personalized stroke risk [218]. Advanced plaques characterized by a large lipid-rich necrotic core and thinning/rupture of the fibrous cap are associated with an increased risk of ischemic cerebrovascular events by 3-fold (95% CI: 1.51-5.95) and almost 6-fold (95% CI: 2.65-13.30), respectively [114].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the time range of follow-up in the studies is not long term; hence, it is vital that future studies take into consideration the relationship of time with the outcomes of the interventions if longer durations are considered. Very few studies focused on the predictors and patient characteristics that could also benefit patient selection for the appropriate modality [34].…”
Section: Limitationsmentioning
confidence: 99%
“…Globally, stroke is a major cause of mortality and permanent disability, 1 and ischemic stroke (IS) is closely associated with carotid plaques. 2 Previous research focusing on plaque morphology points out that plaque vulnerability is characterized by a large necrotic core, high macrophage content, a concomitant reduction in collagen, and a thin fibrous cap (<65 μm). [3][4][5][6][7] Nevertheless, studies have shown that plaque morphology alone was not enough to predict plaque rupture.…”
Section: Introductionmentioning
confidence: 99%